Pan Trinbago to Attend Govt Sponsored Talks - Unknown (Trinidad Guardian)
Steelband representatives of Pan Trinbago have voted to attend Government's National Consultation on Steelband, scheduled for January 29. This decision was taken with the understanding that Pan Trinbago is officially registered as a union prior to the consultation. There was also agreement to urge government to consider awarding scholarships to suitably qualified steelbandsmen to be involved in the research and development of the steelband movement.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Steel drum (Musical instrument) -- Research; Pan Trinbago (Organization); Steel band music -- Trinidad and Tobago